Perda de matéria orgânica dissolvida por células flutuantes de cianobactérias potencialmente tóxicas expostas a altas intensidades de luz - Santos, Roseli Machado dos (2006)
Anabaena spiroides and Microcystis aeruginosa are cyanobacteria that frequently bloom in Barra Bonita Reservoir. These floating organisms and the characteristic turbulence found at the reservoir exposure the cells to higher light intensities by lifting them from lower depths in the photic column to surface. The sudden exposure at higher irradiance could cause photoinhibition and photooxidation. This phenomenon could liberate high amounts of dissolved organic matter. This work aimed to investigate the carbon fixation photoinhibition in cells of A. spiroides and M. aeruginosa exposed to high irradiances, the chlorophyll photooxidation and the DOM released by cells of cultures differing in their physiologic state, after exposure to high irradiances through time at laboratory and field investigations. A. spiroides suffered photoinhibition and liberation of dissolved organic matter when exposed to irradiances higher than their EK during four hours as well as when exposed to irradiance of 2000 µmol.m-2.s-1 for eight hours. M. aeruginosa did not present photoinhibition in any case, however, their C14OD liberation was significantly increased. The higher indexes of C14OD excreted by theses cyanobacteria are not apparently due to cell damage. Hence it might represent an adaptation factor to higher irradiances. Similar results were found in experiments incubated in Barra Bonita reservoir.